2020
DOI: 10.3390/pharmaceutics12020134
|View full text |Cite|
|
Sign up to set email alerts
|

Absorption and Intestinal Metabolic Profile of Oleocanthal in Rats

Abstract: Oleocanthal (OLC), a phenolic compound of extra virgin olive oil (EVOO), has emerged as a potential therapeutic agent against a variety of diseases due to its anti-inflammatory activity. The aim of the present study is to explore its in vivo intestinal absorption and metabolism. An in situ perfusion technique in rats was used, involving simultaneous sampling from the luminal perfusate and mesenteric blood. Samples were analysed by UHPLC–MS–MS for the presence of oleocanthal (OLC) and its metabolites. OLC was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 44 publications
4
44
2
Order By: Relevance
“…Besides, the idea of the in-situ perfusion studies is to omit the solubility and evaluate the permeability. While the results provided do not support (-)-oleocanthal as a BCS class II compound, the authors' discussion of (-)-oleocanthal BCS classification is confusing and not justified [1]. Did the authors conclude that (-)-oleocanthal is a BCS class II compound based on presented results, or based on its assumed physicochemical properties (low solubility and relatively high lipophilicity)?…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Besides, the idea of the in-situ perfusion studies is to omit the solubility and evaluate the permeability. While the results provided do not support (-)-oleocanthal as a BCS class II compound, the authors' discussion of (-)-oleocanthal BCS classification is confusing and not justified [1]. Did the authors conclude that (-)-oleocanthal is a BCS class II compound based on presented results, or based on its assumed physicochemical properties (low solubility and relatively high lipophilicity)?…”
Section: Discussionmentioning
confidence: 87%
“…The authors of López-Yerena et al (2020) [1] neither declared the purity of the used (-)-oleocanthal by any analytical technique nor did they attempt to confirm its identity by any chromatographic and/or spectroscopic tools. This is very important due to the high instability and sensitivity of S-(-)-oleocanthal to air, light, and moisture, and the close structural similarity of several related secoiridoids present in EVOO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This data proposes that oleocanthal plays a key role in the modulation of inflammatory processes at the level of adipose tissue and could therefore improve the chronic low-grade inflammatory state, typical of obesity-related diseases and MetS [ 266 ]. However, in vivo pharmacokinetic studies conducted in rats demonstrated a low intestinal absorption of oleocanthal [ 278 ]. Human studies investigating the oleocanthal bioavailability after EVOO assumption are limited.…”
Section: Possible Effects Of Natural Bioactive Compounds In Metabomentioning
confidence: 99%